Role of community engagement in advancing vaccine equity - Smith, Samantha; Marquez, Erika; Haboush-Deloye, Amanda; Tu, Tiana; Goodie, Aaliyah; Perez, David (Frontiers in Public Health, 2024)
The COVID-19 pandemic exacerbated existing health disparities among historically and currently underserved, underresourced, and marginalized communities worldwide. These communities faced disproportionate COVID-19 morbidity and mortality and were generally less likely to receive a COVID-19 vaccine once it became widely available to the public. Community engagement is an approach that can help bridge these inequities. This community case study adapted and implemented an existing community engagement framework to tailor a statewide vaccine equity effort that addresses community-specific priorities during a public health emergency. The adapted framework includes the following key phases: 1) creating an environment for community engagement; 2) making the work relevant; 3) narrowing the focus; 4) planning and conducting the work; and 5) evaluating the work. All of these supported the successful establishment of a statewide collaboration that consisted of various partners from various sectors who shared a collective commitment to increase COVID-19 vaccine confidence and address barriers to vaccination among the diverse communities in Nevada. Ultimately, a community engagement framework can provide a roadmap to navigate the dynamic and multifaceted nature of equity-related work by paving the way for meaningful interventions to mitigate health disparities.